Certainty and systematicity of practice-derived evidence matter for its relative importance in professional decision-making: Survey results on the role of proven experience in Swedish medicine, nursing, OT, dentistry, and dental hygiene. (December 2022) - Persson, Johannes; Wallin, Annika; Dewitt, Barry; Wahlberg, Lena
Abstract: Background: High-quality healthcare decisions need to balance input from science and clinical practice. When two sources of evidence — such as scientific and practice-derived evidence — are compared, integrated, or need to stand-in for one another, they need to be comparable on similar dimensions. Since 1891, Swedish physicians have been operating under a legal requirement to base their healthcare decisions on science and "proven experience" (approximately clinical expertise), and today all healthcare personnel in Sweden fall under this legal requirement. Objectives: We investigated the dynamics between these two kinds of evidence with respect to importance, systematicity, and certainty by studying Swedish healthcare professionals. Design: Survey to professionals; document studies of political discourse. Method: In this study, a survey was sent to simple random samples of Swedish professionals in medicine, nursing, occupational therapy, dentistry, and dental hygiene, asking about the roles of science and proven experience in medical decision making. Outcome measures were how important, certain, and systematic science and proven experience are for successful medical decision making. Participants: The sampling frame was each profession's most recent occupational registry accessed by the Swedish federal statistical agency. 3500 surveys were distributed. 1626 surveys were returned. 26 participants were removed prior to analysis (exclusion criteria: more than one profession indicated, missing certificate, and mistake in stratum). The final sample consisted of 295 physicians, 300 nurses, 365 occupational therapists, 339 dentists, and 301 hygienists. 162 responses in questions used as variables in the analyses were either uninterpretable or empty; those were replaced with the modal response for a given participant's profession on a given question. Results: In the study, proven experience's perceived importance for clinical decision making is positively correlated with its certainty and systematicity, and an increased certainty and systematicity is positively correlated with a diminished difference in importance between science and proven experience for almost all professions surveyed in this study. Conclusions: Proven experience has an evidentiary role in clinical decision making, and this role depends in part on its certainty and systematicity. Notably, this makes the EBM-based perspective that practice-derived knowledge is primarily of implementation value less plausible.